The Effect of Spiritual Skills Training on the Quality of Life of Family Caregivers of Hemodialysis Patients - Maasoumeh Barkhordari-Sharifabad; Najmeh-Sadat Mousavi (Hamadan University of Medical Sciences, 2022)
Background and Objective: The responsibility and concerns of caregivers of hemodialysis patients can impair their quality of life. Since spirituality, as one of the dimensions of human existence, plays an important role in the ability to cope with stress, the present study aimed to determine the effect of spiritual training programs on the quality of life in the caregivers of hemodialysis patients. Materials and Methods: The design of this study was the comparison of outcomes before and after a planned intervention without the use of a control. It was conducted on 30 family caregivers of hemodialysis patients who were referred to the Dialysis Center of Tabas in 2019. The subjects were selected via the convenience sampling method. The intervention was spiritual skills training, which was conducted orally in seven sessions of 45 to 60 minutes once a week. Before and after the intervention, a valid and reliable questionnaire on caregivers' quality of life was completed by the caregivers. The data were analyzed in SPSS software (version 20) using descriptive and inferential statistical tests. Results: There was a statistically significant difference between the overall quality of life and mental concerns before and after the intervention (P<0.05). This difference was not significant in the dimensions of care burden, conflict, self-actualization, and positive perception of situations (P>0.05). Conclusion: Teaching spiritual skills exerted a positive effect on the quality of life among the caregivers of hemodialysis patients. Therefore, the development of spiritual skills training programs for caregivers can be of great help in improving their quality of life.